Spectroscopic Characterization of Carbon Chains, Ions, and Cluster Ions - John P. Maier (CHIMIA)
The current directions and experimental techniques used for the measurement of the electronic spectra of astrophysically relevant carbon chains, as well as infrared spectra of ionic complexes are outlined.